ANALISIS KESALAHAN KATA BANTU KETERANGAN â€œYUAN LAIâ€ DAN â€œBEN LAIâ€ PADA ANGKATAN 2015 PENDIDIKAN BAHASA MANDARIN - Irwan, Irwan; Ina, Ina; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractChinese adverbs "yuanlai" and "benlai" are one of the most commonly used time adverbs in Chinese. Both words use adverbs of time. In addition, the use of different adverbs can change the meaning of a sentence. In the process of learning, Chinese learners sometimes misuse the understanding of "yuanlai" and "benlai". The author test the students of Chinese Tanjungpura University in 2015 using "yuanlai" and "benlai" to analyze the student errors and find out the reasons. From the results of the test, the author concludes that the error rate of student using "yuanlai" and "benlai" adverbs is 52.15%, and the correct rate is 47.85%. The students errors in using adverbs of "awalnya" and "sebenarnya" are due to the difficulty of grammatical "yuanlai" and "benlai". The test results show that the subjects do not grasp the usage very well in the process of learning these two adverbs. The author also understands that the common types of errors in students learning are misrepresentation errors and misorder errors. Keywords: Yuanlai and Benlai, Time Adverbs, Errors Analysis